2017
DOI: 10.1128/mbio.01969-16
|View full text |Cite
|
Sign up to set email alerts
|

The Source and Evolutionary History of a Microbial Contaminant Identified Through Soil Metagenomic Analysis

Abstract: In this study, strain-resolved metagenomics was used to solve a mystery. A 6.4-Mbp complete closed genome was recovered from a soil metagenome and found to be astonishingly similar to that of Delftia acidovorans SPH-1, which was isolated in Germany a decade ago. It was suspected that this organism was not native to the soil sample because it lacked the diversity that is characteristic of other soil organisms; this suspicion was confirmed when PCR testing failed to detect the bacterium in the original soil samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…This study made use of many different previously analyzed infant datasets. These datasets have previously published descriptions of the study design, patient selection, and sample collection, and are referred to as NIH1 [51, 52], NIH2 [19], NIH3 [53], NIH4 [54], Sloan2 [19], and SP_CRL [55]. Infants were chosen for inclusion in this study irrespective of fungal disease state.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study made use of many different previously analyzed infant datasets. These datasets have previously published descriptions of the study design, patient selection, and sample collection, and are referred to as NIH1 [51, 52], NIH2 [19], NIH3 [53], NIH4 [54], Sloan2 [19], and SP_CRL [55]. Infants were chosen for inclusion in this study irrespective of fungal disease state.…”
Section: Methodsmentioning
confidence: 99%
“…This study also involved the collection and processing of an additional 269 samples from 53 infants. Newly collected infant fecal samples followed the same sample collection and DNA extraction protocol as described previously [53, 56]. Metagenomic sequencing of newly collected infant fecal samples was performed in collaboration with the Functional Genomics and Vincent J. Coates Genomics Sequencing Laboratories at the University of California, Berkeley.…”
Section: Methodsmentioning
confidence: 99%
“…However, through the use of metagenomics ( Brazelton et al, 2012 ), researchers have shown that members of the Betaproteobacteria are in fact ubiquitous and ecologically important members of alkaline (pH > 10) serpentinite environments, which was subsequently verified by culture-dependent studies ( Suzuki et al, 2014 ). Additionally, Olm et al (2017) recovered Delftia genomes from soil metagenome assemblies and were able to show these genomes were from contamination using comparative genomics. Thus, the ability to trace contamination with high precision using techniques that identify strain level variation, gene additions or loss, and the presence of plasmids is at the forefront of this detective work.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the samples from the same infant were all processed at the same time using the same reagents, yet abundances change substantially across the sample series. Additionally, the two Purpureocillium genomes reconstructed from gut samples from different infants are distinct ( Figure 4 ); one would expect the sequences to be more similar if derived from the same reagent contaminants (Olm et al, 2017b) .…”
Section: Eukaryotes In the Nicu Have The Genomic Potential To Colonizmentioning
confidence: 99%